Pocket Oxford Dictionary and Thesaurus - Edited by Hawker, Sara (Oxford Oxford University Press, 2008)
With dictionary and thesaurus entries combined for ease of use, and a fresh, clear design, the Pocket Oxford Dictionary and Thesaurus provides quick solutions to everyday language queries.
Keywords: English language -- English language--Synonyms and antonyms